Pluralism of pluralism : a pluralistic probe into philosophizing - Association of Christian Philosophers of India. Meeting 2005 : Salesian College); Puthenpurackal, Johnson J. (Bangalore : Asian Trading Corp., 2006)
With special reference to India
"Papers presented at the ACPI annual meeting held at Salesian College, Sonada, Darjeeling, 18-22 October 2005."
Includes bibliographical references.
Keywords: Christianity and other religions -- India -- Congresses; Religious pluralism -- Christianity -- Congresses; Religious pluralism -- India -- Congresses